Compensatory strategies for acquired disorders of memory and planning: differential effects of a paging system for patients with brain injury of traumatic versus cerebrovascular aetiology. Issue 8 (26th November 2007) - Fish, J; Manly, T; Emslie, H; Evans, J J; Wilson, B A
Abstract : Background: Previous studies have demonstrated the effectiveness of paging systems in compensating for everyday memory and planning problems after brain injury, including in individuals with traumatic brain injury (TBI). Methods: Here, in addition to further analyses of the TBI data from a previous randomised control crossover trial, results are reported from a sub-group of 36 participants with brain injury from cerebrovascular accident (CVA). Results: Results indicate that, as with the TBI group, the pager was effective. However, the pattern of results following cessation of treatment differed. At a group level, TBI participants demonstrated maintenance of pager-related benefits, whereas CVA participants' performance returned to baseline levels. Comparisons of demographic and neuropsychological characteristics of the groups showed that the CVA group was older, had a shorter interval post-injury, and had poorer executive function than the TBI group. Furthermore, within the TBI group, maintenance was associated with executive functioning, such that executive dysfunction impeded maintenance. This correlation remained after controlling for demographic differences between groups. Conclusions: Together, these findings suggest that executive dysfunction may affect treatment—for example, whether or not temporary use of the pager is sufficient to establish a subsequently self-sustaining routine.